2021
DOI: 10.1007/s00265-021-03041-0
|View full text |Cite
|
Sign up to set email alerts
|

Neophobia in 10 ungulate species—a comparative approach

Abstract: Neophobia (the fearful reaction to novel stimuli or situations) has a crucial effect on individual fitness and can vary within and across species. However, the factors predicting this variation are still unclear. In this study, we assessed whether individual characteristics (rank, social integration, sex) and species socio-ecological characteristics (dietary breadth, group size, domestication) predicted variation in neophobia. For this purpose, we conducted behavioral observations and experimental tests on 78 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 141 publications
(175 reference statements)
1
21
0
Order By: Relevance
“…Future studies could examine whether offering the pellets with other feedstuffs improves palatability (and possibly familiarity), but this would reintroduce the need for additional meal components in the test and change the interpretation. Levels of neophobia in ungulates differ between individuals 34 and overall, the pellets were unacceptable to 15.9% of the animals tested. In these instances, the test could not be adequately performed, so selection of a different form of the OGT where voluntary intake is not required is suggested for these animals.…”
Section: Discussionmentioning
confidence: 90%
“…Future studies could examine whether offering the pellets with other feedstuffs improves palatability (and possibly familiarity), but this would reintroduce the need for additional meal components in the test and change the interpretation. Levels of neophobia in ungulates differ between individuals 34 and overall, the pellets were unacceptable to 15.9% of the animals tested. In these instances, the test could not be adequately performed, so selection of a different form of the OGT where voluntary intake is not required is suggested for these animals.…”
Section: Discussionmentioning
confidence: 90%
“…The behaviour of animals is also significantly influenced by changes in their habitats, which are most easily noticed by them in non-urbanized environments ( Vincze et al, 2015 ; Zhou and Liang, 2020 ; Mikula et al, 2021 ). The fear of novel stimuli, called neophobia, plays a major role in animal ecology including animal behaviour ( Crane and Ferrari, 2017 ; Schaffer et al, 2021 ). Because predation is one of the major factors shaping animal populations ( McNamara and Houston, 1987 ; Gilg et al, 2003 ), we assumed that the appearance of a new, unknown stimulus in a given area should trigger an appropriate reaction reflected in changes in the behaviour of potential victims, feeling a potential threat.…”
Section: Discussionmentioning
confidence: 99%
“…birds: Milvago chimango , Biondi, Bo, & Vassallo, 2010; Guido, Biondi, Vasallo, & Muzio, 2017; mammals: Cebus apella , Visalberghi, Janson, & Agostini, 2003), but it rarely differs across the sexes (e.g. birds: Passer domesticus , Ensminger, Westneat, & Zeh, 2012; mammals: 10 ungulate species, Schaffer et al, 2021; but see Crane & Ferrari, 2017 and Crane et al, 2020 for a short discussion). Furthermore, neophobia can be influenced by the social environment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…birds: 10 corvid species, Miller et al, 2022; Taeniopygia guttata , St. Lawrence, Rojas Ferrer, & Morand-Ferron, 2021; mammals: Bos taurus taurus ; Meagher et al, 2015; 10 ungulate species, Schaffer et al, 2021) and might negatively influence other cognitive processes such as learning (e.g. birds: Milvago chimango, Guido et al, 2017) but not all studies found such a link (e.g.…”
Section: Introductionmentioning
confidence: 99%